2020
DOI: 10.3390/s20185340
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cattle Social Transitional Behaviour: Attraction and Repulsion

Abstract: Understanding social interactions in livestock groups could improve management practices, but this can be difficult and time-consuming using traditional methods of live observations and video recordings. Sensor technologies and machine learning techniques could provide insight not previously possible. In this study, based on the animals’ location information acquired by a new cooperative wireless localisation system, unsupervised machine learning approaches were performed to identify the social structure of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…This consistency in how individual heifers interact with the virtual fence across contexts could point to an underlying temperamental predisposition. Cattle vary in their willingness to spend time away from the herd (Hirata et al, 2013;Xu et al, 2020), while ecological studies show that bolder, asocial and exploratory individuals are more likely to disperse from their resident social group (reviewed by Cote et al, 2014). Verdon et al (2020) found bold heifers were more likely to ignore the audio and electrical stimuli delivered in a feed attractant trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consistency in how individual heifers interact with the virtual fence across contexts could point to an underlying temperamental predisposition. Cattle vary in their willingness to spend time away from the herd (Hirata et al, 2013;Xu et al, 2020), while ecological studies show that bolder, asocial and exploratory individuals are more likely to disperse from their resident social group (reviewed by Cote et al, 2014). Verdon et al (2020) found bold heifers were more likely to ignore the audio and electrical stimuli delivered in a feed attractant trial.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of cues delivered to heifer 9 may thus be higher in allocation 3 than reported. movement patterns than others (i.e., herd "leaders"- Reinhardt and Reinhardt, 1981;Dumont et al, 2005;Ramseyer et al, 2009;Keshavarzi et al, 2020;Xu et al, 2020). Leadership is not synonymous with dominance, but group leaders are likely to be animals that are less sociable, more bold and more explorative (Stricklin and Kautz-Scanavy, 1984;Ramseyer et al, 2009;Della-Rossa et al, 2013;Neave et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of on-animal sensors and technologies such as GPS devices [ 14 , 15 ], proximity loggers [ 9 , 16 ], or ultra-wideband positional loggers [ 17 , 18 ] there is the potential to deploy these devices on livestock individuals within groups to enable more accurate monitoring of position and/or social relationships. The data from these sensors can provide new insights into how individuals in a group interact and/or influence each other, including affiliative and/or agonistic relationships between group members [ 19 , 20 ], network structure [ 19 ], and resource-use patterns [ 21 ]. Commercially, sensor technologies that allow quantification of social interactions may, for example, enable understanding of how animals learn new technologies such as virtual fencing [ 22 ], detect male-female interactions to determine oestrus [ 23 ] and mating [ 24 ], allow maternal pedigree detection through ewe-lamb contact [ 25 ], or could monitor grazing behaviour [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more frequent and accurate data collection to capture all possible social interactions will result in more precise sub-groupings and allow detection of the social network structure within the group. In addition, more precise data may enable researchers to quantify interactions in situations where animals are all in close physical contact [ 20 ]. While GPS tracking has been used to quantify social relationships between livestock animals [ 30 , 31 , 32 ], GPS typically has a high spatial precision error; one study showed an overestimation of 15.2% or 1.5 km for daily cattle travels without any data filtering [ 33 ], another study showed a contact distance error of 9.5 m with prototype proximity-logging GPS collars on bighorn sheep [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clustering algorithms, by virtue of their incredible flexibility, have successfully been applied to a range of PLF data streams [ 7 , 13 , 14 , 15 , 16 , 17 , 18 ]. In our own previous work, we have highlighted the utility of hierarchical clustering-based approaches in leveraging the behavioral co-dependencies of cows housed socially in large groups, in a production environment, in order to recover complex temporal patterns in behavior [ 7 ].…”
Section: Introductionmentioning
confidence: 99%